Spoken Dialogue Systems for Ambient Environments Second International Workshop on Spoken Dialogue Systems Technology, IWSDS 2010, Gotemba, Shizuoka, Japan, October 1-2, 2010. Proceedings - Lee, Gary Geunbae; Mariani, Joseph; Minker, Wolfgang; Nakamura, Satoshi; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2010)
This book constitutes the refereed proceedings of the Second International Workshop on Spoken Dialogue Systems, IWDS 2010, held in Gotemba, Japan, in October 2010. The 22 session papers presented together with 2 invited keynote talks were carefully reviewed and selected from numerous submissions. The papers deal with topics around Spoken Dialogue Systems for Ambient Environment and discuss common issues of theories, applications, evaluation, limitations, general tools and techniques.
Long Papers -- Impact of a Newly Developed Modern Standard Arabic Speech Corpus on Implementing and Evaluating Automatic Continuous Speech Recognition Systems -- User and Noise Adaptive Dialogue Management Using Hybrid System Actions -- Detection of Unknown Speakers in an Unsupervised Speech Controlled System -- Evaluation of Two Approaches for Speaker Specific Speech Recognition -- Issues in Predicting User Satisfaction Transitions in Dialogues: Individual Differences, Evaluation Criteria, and Prediction Models -- Expansion of WFST-Based Dialog Management for Handling Multiple ASR Hypotheses -- Evaluation of Facial Direction Estimation from Cameras for Multi-modal Spoken Dialog System -- D3 Toolkit: A Development Toolkit for Daydreaming Spoken Dialog Systems -- New Technique to Enhance the Performance of Spoken Dialogue Systems by Means of Implicit Recovery of ASR Errors -- Simulation of the Grounding Process in Spoken Dialog Systems with Bayesian Networks -- Facing Reality: Simulating Deployment of Anger Recognition in IVR Systems -- A Discourse and Dialogue Infrastructure for Industrial Dissemination -- Short Papers -- Impact of Semantic Web on the Development of Spoken Dialogue Systems -- A User Model to Predict User Satisfaction with Spoken Dialog Systems -- Sequence-Based Pronunciation Modeling Using a Noisy-Channel Approach -- Rational Communication and Affordable Natural Language Interaction for Ambient Environments -- Construction and Experiment of a Spoken Consulting Dialogue System -- A Study Toward an Evaluation Method for Spoken Dialogue Systems Considering User Criteria -- A Classifier-Based Approach to Supporting the Augmentation of the Question-Answer Database for Spoken Dialogue Systems -- The Influence of the Usage Mode on Subjectively Perceived Quality -- Demo Papers -- Sightseeing Guidance Systems Based on WFST-Based Dialogue Manager -- Spoken Dialogue System Based on Information Extraction from Web Text.
Keywords: Computer science; Information storage and retrieval systems; Information systems; Artificial intelligence; Computer vision; Optical pattern recognition; Computer Science; Artificial Intelligence (incl. Robotics).; User Interfaces and Human Computer Interaction; Information Systems Applications (incl.Internet).; Information Storage and Retrieval; Pattern Recognition; Image Processing and Computer Vision